Ethnomathematics and Ethnoscience Analysis of Aru Culture Related to Mathematics and Science Concepts at Elementary School - Moriolkosu, Andarias Dereck; Dewanti Handayani, Sri Sulastri; Sunarso, Ali (Educational Management, 2020)
Ethnomathematics and ethnoscience are approaches related to culture in mathematics and science. Indonesia is a country that has many islands and ethnicities. Therefore, many cultures need to be explored and connected with concepts of mathematics and science and they can be implemented in the learning process. The culture that can be integrated into mathematics and science is known as ethnomathematics and ethnoscience. The aims of this study were to describe the exploration results of ethnomathematics and ethnoscience forms of North Aru Sub-district culture, to obtain the analysis results of the relationship between ethnomathematics and ethnoscience forms and their concepts at elementary school. This study was a qualitative descriptive exploration design with an ethnographic approach. The data of the study were obtained from society, their activities, and artifacts. The data collection method were observation, interviews, and documentation. The data were analyzed using triangulation techniques. The results of the study showed that the forms of ethnomathematics and ethnoscience of North AruSub-district culture explored were the concepts of mathematics and science among traditional games, traditional houses, traditional food, fishing gears, art instruments, wickets, and tradition. The forms of ethnomathematics and ethnoscience were related to the concepts of mathematics and sciences, covering a square, rectangular, triangle, hexagon, trapezium, tube, force, and natural resources. The researchers suggested teachers (a) apply cultural-based learning so that students can recognize cultural elements in their area, (b) to preserve the local culture.cultural elements in their area, (b) to preserve the local culture.